Data Analysis and Processing Application of Deep Learning in Engineering Cost Teaching Evaluation - Xiang He; Shuzhe Fu (Journal of Mathematics)
Based on the poor quality of engineering cost teaching, this paper puts forward the application method of in-depth learning in engineering cost teaching evaluation. This study aims to construct the engineering cost teaching evaluation system, optimize the engineering cost teaching evaluation algorithm combined with the in-depth learning method, standardize the evaluation index of the engineering cost teaching system, and realize the research goal of engineering cost teaching evaluation. Finally, the experiment proves that the application effect of in-depth learning in engineering cost teaching evaluation is obviously better, which can better guide the quality of engineering cost teaching.